2020
DOI: 10.30534/ijeter/2020/2481.12020
|View full text |Cite
|
Sign up to set email alerts
|

On the Existence of Attempted Leader in Tropical Thunderstorm

Abstract: This report is a novel initiative at analysing and characterizing attempted leader in Melaka, Malaysia which located at vicinity of tropic region. The electric fields generated by the lightning were recorded using High Speed Transient Recorder (Lecroy HDO4024) with 90 nanosecond resolution in 2 seconds duration. This study examined a total of 237 electric radiation field recorded from three thunderstorms in 1 January 2019 to 3 January 2019. Uniquely, the attempted leader from 5 samples only appeared as positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
0
6
3
Order By: Relevance
“…4. The whole pulse train of positive polarity in this paper (3.47 ms) shows the shortest duration (by two factors) compared to the positive initial polarity of those isolated pulse trains reported by [13] (7.4 ms) and [16] (6.9 ms). As compared to the negative attempted leader, the present study shows a slightly greater result than [12] (2.7 ms), however, four factors greater than [16] (0.98).…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…4. The whole pulse train of positive polarity in this paper (3.47 ms) shows the shortest duration (by two factors) compared to the positive initial polarity of those isolated pulse trains reported by [13] (7.4 ms) and [16] (6.9 ms). As compared to the negative attempted leader, the present study shows a slightly greater result than [12] (2.7 ms), however, four factors greater than [16] (0.98).…”
Section: Resultscontrasting
confidence: 46%
“…As result, there will be no return stroke observed. In this case, it was reported as attempted leaders by [12] and [13] and also as isolated breakdown pulse train by [14]- [16]. This type of initial breakdown is known as an "attempted leader" throughout this study.…”
Section: Introductionmentioning
confidence: 87%
“…Based on the comparison, it was found that the arithmetic methods using autoanalysis software for the combination of fast transition and zero time crossing parameters detection in this study is appropriate and reliable since the determination of the autoanalysis software is comparable with the manual analysis. It will be interesting and enhance more understanding on auto-analysis study if one can consider this type of analysis by considering the uncommon lightning mechanism such as attempted leader as reported by [23], [54] while, common lightning flashes such as reported by [19], [24], [55], [56]. For future works, the technique of time-frequency distributions (TFDs) analysis for detection and classification of the lightning return stroke will be explored since this technique can solve a big sample and complexity of the variety of the parameters [13], [16], [52], [57].…”
Section: Resultsmentioning
confidence: 99%
“…Lightning has both direct and indirect effects on power system performance, with transient high voltages causing flashover on electrical equipment on the power [28]. In other words, attempted leader is the potential cloud-to-ground lightning flash, however the downward moving step leaders die out before being attached with the progressing upward leaders as reported by previous researchers such as [22]- [23], [37]- [39]. This study presents the novel information in large scale of data of attempted leader distribution activities with the correlation of number of thunderstorms producing it with the influence of climatology condition, or monsoon seasons at location of tropical region Melaka, Malaysia.…”
Section: Introductionmentioning
confidence: 92%
“…Negative CG flashes take place between the main negative charge center and ground [14]- [18] while positive CG flashes take place between the positive charge center and the ground [19]- [21]. However, there are condition where the first step leader cannot propagate to the ground completely and this event was terminologically referred as 'attempted leader' [22], [23]. Furthermore, 1325 the large current running in the return stroke of most lightning strikes causes damage, as does the heat generated by this and the continuing current [24]- [30].…”
Section: Introductionmentioning
confidence: 99%